If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + 2 = m + -3 Combine like terms: -20 + 2 = -18 -18 = m + -3 Reorder the terms: -18 = -3 + m Solving -18 = -3 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -18 + -1m = -3 + m + -1m Combine like terms: m + -1m = 0 -18 + -1m = -3 + 0 -18 + -1m = -3 Add '18' to each side of the equation. -18 + 18 + -1m = -3 + 18 Combine like terms: -18 + 18 = 0 0 + -1m = -3 + 18 -1m = -3 + 18 Combine like terms: -3 + 18 = 15 -1m = 15 Divide each side by '-1'. m = -15 Simplifying m = -15
| 19x-7=15x+9 | | 7x-16=29-2x | | 3/x=3/4x+3 | | 2x+4+24=108 | | 4r-3+2r=3 | | 3x+2-x+x=x+6 | | n/4=17/3 | | 20e^8t=12e^5t | | 3x+6=45-5x-20 | | 9-1(x-5)=4 | | 5x+8=-9x+64 | | (xy+1)dx+x(x+4y-2)dy=0 | | 4-1/9x=10/3 | | -9=-3(x-3) | | j-8.4=25.2 | | 2(7)-9y=14 | | 11x+14=4x+56 | | (x^2)+9x=3cost | | 16x^2-4x-12=0 | | k^2-4k-12=0 | | 3(2-x)-3-x+4=2-x+5 | | -2x^2+3x-7=-9 | | 2x+6=24x+4 | | 2x^5+6x^2+8x=0 | | 5(8-2y)-2y=4 | | 9=4x-7/3 | | x/3+56=14 | | 2=+2x+13x+2x | | 60+10x=25x | | 2=+9x+13x+2x | | 4=+9x+13x+2x | | 2.3y-9.5=-9.7 |